2014
DOI: 10.1080/08946566.2013.867242
|View full text |Cite
|
Sign up to set email alerts
|

Older People’s Perceptions of the Term Elder Abuse and Characteristics Associated With a Lower Level of Awareness

Abstract: A national representative survey of 2,021 community-dwelling older people was carried out in 2010 using face-to-face interviews. The study examined how the term "elder abuse" was understood by this population and identified factors associated with lower levels of awareness. Over 80% of this population recognized the term elder abuse, and 56% demonstrated specific insight related to typologies, locations, and perpetrators of abuse. Less specific responses were given by 22% of participants, and a further 21% cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…A study from Ireland [26] found that household income is relevant risk factor for older people being abused. Similarly as in the Macedonian study respondents who say that the total family income cannot completely satisfy their needs increase 1.4 times more the likelihood of older persons to experience abuse.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Ireland [26] found that household income is relevant risk factor for older people being abused. Similarly as in the Macedonian study respondents who say that the total family income cannot completely satisfy their needs increase 1.4 times more the likelihood of older persons to experience abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence studies in the UK4 found that 2.6% of people aged 66 and over living in private households experienced abuse, and a similar study in Ireland3 indicated a prevalence of 2.2%. These studies also show that elderly victims of abuse are in frequent contact with health care services, but few report the abuse 3,4. Elderly people may tend to play down abuse problems or regard it as a private matter 3,5,6.…”
Section: Introductionmentioning
confidence: 95%
“…Long-term abuse impacts physical health and quality of life, and is associated with an increased risk of morbidity and mortality 1,2. There is a clear connection between elderly abused people, disability and low social support 2,3. The Irish prevalence study3 emphasized that older abused people with poor community support tended to report abuse three times more than those with stronger support.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations